P104 Inflammatory complications of the pouch, and therapetic requirements after colectomy in patients with ulcerative colitis. Results from the RESERVO Study of GETECCU. (27th May 2021) - Mesonero Gismero, F; Zabana, Y; Fernández-Clotet, A; Sola, A; Caballol, B; Leo, E; García, M J; Bertoletti, F; Alejandro, M; Suris, G; Casis, B; Ferreiro-Iglesias, R; et al.
Abstract: Background: Pouchitis and other inflammatory pouch diseases (IPD) are frequent in pouch-carrying patients operated for a previous diagnosis of ulcerative colitis. We evaluated characteristics and differences in therapeutic requirements between pouchitis, Crohn′s-like disease of the pouch (CDP) and cuffitis. Methods: This is a retrospective and multicentric Spanish cohort of GETECCU (RESERVO Study), including pouch-carrying patients (operated 1995 to 2016) with previous ulcerative colitis, ileostomy closure and subsequent diagnosis of IPD (pouchitis, CDP or cuffitis), following ECCO diagnostic criteria 1 . Follow up extended to June 2020. Pouchitis was categorized attending current classifications. Use of medical and surgical therapies was collected and differences between pouchitis and CDP were analyzed using descriptive and comparative statistics. Results: A total of 338 patients were included. Demographic and clinical characteristics are presented in Table 1. The most frequent IPD was pouchitis (n=258, 76%), followed by CDP (n=55, 16%) and cuffitis (n=25, 7.4%). Pouchitis was diagnosed at a median time of 27 (range 1–342) months. Prevalence according to pouchitis classification is presented in Figure 1. CDP was diagnosed at a median time of 77 (range 5–324) months, around 75% with a previous pouchitis diagnosis. Location of CDP (not mutually excludent) was pouch CDP (91%), 87% pre-pouch ileitis, and 41% perianal disease. Regarding behavior: 26 (47%) were inflammatory, 12 (22%) stricturing and 17 (31%) penetrating (8 rectovaginal fistulas). Cuffitis was diagnosed at a median time of 18 (range 1–219) months. Medical and surgical therapies used are shown in Figure 2. Immunosuppressants (58.2 vs 22.4%, p 0.001), biologics (74.5 vs 34.8%, p 0.0001), and surgery (41.8 vs 21.3%, p 0.003) were more used in CDP than in pouchitis. Conclusion: Pouchitis and CDP are heterogeneous inflammatory pouch complications with a wide and high therapeutic requirement. CDP presents a later diagnosis and has higher therapeutic needs than pouchitis. 1. Fernando Magro, Paolo Gionchetti, Rami Eliakim et al, for the European Crohn's and Colitis Organisation [ECCO], Third European Evidence-based Consensus on Diagnosis and Management of Ulcerative Colitis. Part 1: Definitions, Diagnosis, Extra-intestinal Manifestations, Pregnancy, Cancer Surveillance, Surgery, and Ileo-anal Pouch Disorders, J Crohns Colitis 2017; 11(6): 649–670.